Motivation to read and reading proficiency: a crucial link for students learning English as a second language - Moffatt, Terry (School of Education, 2023)
This dissertation undertakes to investigate the link between the motivation to read and reading proficiency at the Grade Five level. The majority of the study took place in Bahrain in a bilingual English/Arabic private school. Most of the students were not only reading below grade level, but also disliked reading. Similar levels of reading performance and attitudes towards reading were found at Mountain Road Primary School in Woodstock, South Africa, where the second phase of the study took place. This school was used in the research process to provide a comparison to Bahrain Bayan School as well as an indication of progression. The impetus for the study came while I was teaching at Bahrain Bayan School in an effort to find a way to motivate students to do the amount of reading necessary to improve reading proficiency. I chose to implement Literature Circles in the classroom, which is a method that integrates the skills-teaching approach with the “whole-language” approach. Students are exposed to a wide variety of reading materials of their choosing and they read extensively. Group discussions are an integral element and help to generate more interest and involvement in the text. At the same time, focus lessons provide students with the skills and strategies necessary to improve literacy. The two hypotheses that drove the research were: - Underachievement in reading is largely due to lack of motivation to read; - Students' background, i.e. early access to books, parental reading habits and so on; is an important factor In reading motivation The outcomes of the research done at Bahrain Bayan School indicate that there Is a link between motivation to reading and reading proficiency. The significance of social-environmental influences was also proven to be an important determinant of reading success. The comparison with Mountain Road Primary School is useful in that it indicates similar difficulties in a multilingual context. There is good evidence that if a similar program were to be followed as at Bahrain Bayan School, there is a good chance that reading proficiency would Improve.